A Novel Surgical Technique for the First Case of Neglected Bilateral Severe Congenital Genu Recurvatum Combined with Bilateral Talipes Equinocavovarus - Kuan-Lin Liu; Ting-Yu Hung; Xin-Le Eng; Ing-Ho Chen (Medicina)
Congenital genu recurvatum (CGR) is a rare congenital knee deformity that can be diagnosed pre- or postnatally. Most CGR cases are treated during infancy by manipulation and serial casting or splinting. Only a few neglected cases of CGR in adults with the necessity of surgical treatment have been reported. This study presents the first case of neglected bilateral severe CGR combined with bilateral talipes equinocavovarus (BTE) in a 25-year-old woman. This case is unique, because BTE is secondary to CGR with persistent progression into adulthood. The patient underwent two-stage surgeries with 1.5-month intervals to correct the knee and foot/ankle deformities. For CGR, a novel technique that combines posterior closing and anterior open wedge osteotomy was carried out to separately address the issues of 80° and 60° deformity, achieving a total correction of 140° for both knee hyperextension deformities. For BTE, the modified Lambrinudi triple arthrodesis and almost complete plantar fascia release were performed for the treatment of foot/ankle deformities. The patient had no neurovascular problems, and the wounds healed well. After 1 year of hospital-based rehabilitation training, the patient could stand and walk without the help of any walking-assist devices. The outcomes of the three- and nine-year follow-ups were highly satisfactory. Our patient represents a technically challenging case for orthopaedic surgeons because of the complexity of the surgical plan and techniques for the treatment of a patient concurrently having CGR and BTE.